Effect of nitrogen and potassium on growth and development of Curcuma alismatifolia gagnep. - S. Ruamrungsri (2018)
Stubbed rhizomes (without storage root) of Curcuma alismatifolia Gagnep. were planted in soilless medium using sand + rice husk charcoal at the ratio 1:1 (v:v). After shoot sprouting, plants were fertilized with different nutrient solutions three times a week. Three levels of N (50, 100 and 200 mg l-1) combined with three levels of K (50, 100 and 200 mg l-1) were investigated. The results showed that the nitrogen concentration at 200 mg l-1gave the highest results in plant height, number of plants/cluster, diameter of new rhizome, number of new rhizomes, the length of storage root and flower quality. The different levels of potassium tested did not affect these parameters excepted for the number of green bracts and vase life. The optimal levels of nitrogen and potassium for Curcuma alismatifolia Gagnep. growing in the soilless medium was each at 200 mg l-1.